Characterization and Analysis of Bottom Ash Derived from The Combustion of Empty Fruit Bunch (EFB) for Potential Fertilizer - AZZHAR, HANNAH BATRISYIA; Mohd Faizal Tukimon; Amirnordin, Shahrin Hisham; Md Asrul Nasid Masrom; Mohammad Faizal Jabbar (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The palm oil industry generates large quantities of Empty Fruit Bunch (EFB), creating challenges in waste management and environmental sustainability. Combustion is commonly used to reduce EFB volume but the resulting bottom ash is often discarded despite its potential nutrient. This study investigates the characteristics of bottom ash produced from the combustion of EFB pellets to assess its suitability for potential fertilizer applications. EFB pellets were combusted at 200 °C, 300 °C, and 400 °C for 60 minutes inside a combustion chamber under controlled laboratory conditions. Thermogravimetric analysis (TGA) was conducted to evaluate the thermal decomposition behavior of raw EFB, while scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM–EDX) and X-ray diffraction (XRD) were used to analyze ash morphology, elemental composition, and mineralogical phases. The results indicate that increasing combustion temperature enhances mineral crystallinity and reduces residual carbon content. The bottom ash contained essential plant nutrients such as potassium, calcium, magnesium, phosphorus, and silicon, with progressive formation of thermally stable mineral phases at higher temperatures. Among the conditions studied, combustion at 300 °C produced ash with balanced mineral composition and limited sintering, indicating favorable characteristics for agricultural application.